Teaching and learning in the primary school - Pollard, Andrew, 1949-; Bourne, Jill, 1947- (Open University. Postgraduate Certificate of Education., 1994)
This sourcebook offers a unique summary into all that was important in primary education during the 1990s. It provides almost fifty key readings on the field which are grouped around six major topics:* learners* teachers* classrooms* curriculum* assessment* school and education policy. Over half of the readings focus on real life cases - such as pupils, teachers, classrooms or schools - as a means of conveying some of the interpersonal subtleties of teaching and learning in primary schools. At the same time, these cases highlight important current topics and debates in primary education and often provide insights into practical ways of meeting the challenges which are posed. Other articles are more explicitly analytical and provide conceptual frameworks, overviews or critiques of their fields. This is an excellent resource and guide for primary school teachers, and students studying on PGCE courses.